2011
DOI: 10.1111/j.1476-4431.2011.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the efficacy of a veterinary dry heat fluid warmer

Abstract: Although the study device generated statistically significant increases in outflow temperature of crystalloid fluids and pRBC, the ability of the device to decrease the metabolic cost of fluid administration is limited to specific clinical scenarios. The use of prewarmed crystalloid fluids with or without the study device offers minimal benefit over ambient temperature crystalloids. Substantial warming of pRBC occurs during administration, even without use of the study device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 66 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Peter et al suggested that there is no need to warm the infused fluid delivered at flow rates slower than 30 mL/min owing to the minimal change of core body temperature (7). Several studies have demonstrated the effect of administering intravenous fluid in changing the mean body temperature (7,9). According to these studies, when fluid is administered at flow rates >30 mL/min, fluid warming has a preventive effect against hypothermia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peter et al suggested that there is no need to warm the infused fluid delivered at flow rates slower than 30 mL/min owing to the minimal change of core body temperature (7). Several studies have demonstrated the effect of administering intravenous fluid in changing the mean body temperature (7,9). According to these studies, when fluid is administered at flow rates >30 mL/min, fluid warming has a preventive effect against hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…For many decades, several methods have been developed to prevent hypothermia (7)(8)(9)(10). Passive external rewarming is usually used for mild hypothermia.…”
mentioning
confidence: 99%
“…The infusion of warmed fluids can maintain normal body core temperature [10,[12][13][14]. Studies have suggested that fluid warmers are usually unnecessary in adults below a flow of 35 ml.min À1 , which reduces the core body temperature by less 0.5°C, although the effect depends upon body mass [6,8]. Infusate heat loss increases with the length of the intravenous line [10,11,[15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods can limit the development of hypothermia [6][7][8][9][10][11]. Large volumes of intravenous fluid can cool the body core temperature during resuscitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation